Batik Kendil Emas sebagai Warisan Budaya Kabupaten Kendal - Suparti; Parti, Suparti (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2025)
This study examines Batik Kendil Emas as an Indonesian cultural heritage recognized by UNESCO. This batik was launched by Kendal Regency on November 20, 2024, and is inspired by the folktale "Kendil Emas." The batik motif combines local cultural values with modern designs while preserving the traditional elements of Kendal. The collaboration between local government, designers, and local artisans has made this batik a symbol of the identity and pride of the Kendal community. The research uses a descriptive qualitative approach to explore the philosophical meaning, cultural values, and economic potential of Batik Kendil Emas, which plays an important role in cultural preservation, the development of the creative economy, and the promotion of Kendal Regency at both the national and international levels. This batik is also expected to inspire younger generations to preserve local traditions.